High Inequalities Associated With Socioeconomic Deprivation in Cardiovascular Disease Burden and Antihypertensive Medication in Hungary - Boruzs, Klára; Juhász, Attila; Nagy, Csilla; Szabó, Zoltán; Jakovljevic, Mihajlo; Bíró, Klára; Ádány, Róza (Frontiers in Pharmacology, 2018)
The wide life expectancy gap between the old and new member states of the European Union is most strongly related to the high rate of premature mortality caused by cardiovascular diseases (CVDs). To learn more about the background of this gap, the relationship of socioeconomic status (SES) with CVD mortality, morbidity and the utilization of antihypertensive drugs was studied in Hungary, a Central-Eastern European country with an extremely high relative risk of premature CVD mortality. Risk analysis capabilities were used to estimate the relationships between SES, which was char-acterized by tertiles of a multidimensional composite indicator (the deprivation index) and CVD burden (mortality and morbidity) as well as the antihypertensive medications at the district level in Hungary. The excess risks caused by premature mortality from CVDs showed a strong correlation with deprivation using the Rapid Inquiry Facility. The distribution of prevalence values related to these diseases was found to be similar, but in the areas of highest deprivation, where the preva-lence of chronic ischaemic heart diseases and cerebrovascular diseases was found to be higher than the national average by 30% and 20%, the prevalence of hypertension exceeded the national average by only 4%. A linear association between the relative frequency of prescrip-tions/redemptions and deprivation for most antihypertensive drugs, except angiotensinogen re-ceptor blockers, was shown. More intense screening for hypertension is proposed to improve the control of CVDs in coun-tries affected by high disease burden.